Retrieval of a broken sewing needle from the sacrum aided by a permanent magnet: a case report and literature review - Fan Jian; Wang Ming-Ming; Liu Yu-Ping (Open Medicine, 2017)
Penetrating sacral injuries are very rare, but foreign bodies that penetrate the sacrum often cause pain, cerebrospinal fluid leakage, and neurological symptoms. Careful preoperative medical and imaging examinations, determining the position of the foreign body, and surgical exploration are essential in the management of such cases. We present the case of a woman who visited our emergency department with a broken sewing needle in her sacrum. The incident occurred when the patient accidentally sat on the needle while sewing by hand. Pain while sitting was the main clinical finding after the accident. The patient was treated successfully by surgical exploration aided by a permanent magnet. At follow-up a few months later, she was symptom-free. In clinical practice physicians often encounter patients with metallic foreign bodies. Permanent magnets play an important role in the removal of metallic foreign bodies, and emergency department physicians should master the methods and techniques.